La deslegitimación de las armas, el desarme y la protección de la seguridad humana - Jáquez Huacuja, María Antonieta (Revista Mexicana de Política Exterior, 2022)
Disarmament, a subject on which Mexico is acknowledged as an opinion leader, has had a place on the country’s foreign policy agenda for the last 60 years. Yet within the context of modern- day international relations, the keeping of international peace depends on many factors and security issues arise in response to a diversity of events. To speak of disarmament, then, specifically nuclear disarmament, would seem disconnected from reality and the daily concerns of States like Mexico. In this essay, María Antonieta Jáquez asks whether the goal of general and complete disarmament is practicable or whether we should be rethinking our position on the disarmament agenda in light of the realities of the 21st century. The vast majority of rules, perceptions, institutional practices and multilateral negotiating strategies on disarmament —as of early 2011 there were 20 500 nuclear warheads in the world— are a reflection of the state-centric, confrontational power structure of the Cold War years and despite its best efforts, the machinery of disarmament has not yet managed to create legal instruments for the banning of nuclear arms. In light of this, Jáquez offers two recent examples of the successful prohibition of conventional weapons (antipersonnel landmines and cluster munitions), which serve as a lesson in the building of a new style of multilateralism that has negotiated tough regulatory standards outside the traditional multilateral forums for disarmament. According to the author, these experiences can help guide Mexico’s contributions to the nuclear disarmament cause, from a new standpoint that seeks the deligitimization of such weaponsto protect human security, with the focus being on the security of the individual as opposed to that of the State.